2014
DOI: 10.5465/amj.2012.0393
|View full text |Cite
|
Sign up to set email alerts
|

Managing to Stay in the Dark: Managerial Self-Efficacy, Ego Defensiveness, and the Aversion to Employee Voice

Abstract: Soliciting and incorporating employee voice is essential to organizational performance, yet some managers display a strong aversion to improvement-oriented input from subordinates. To help to explain this maladaptive tendency, we tested the hypothesis that managers with low managerial self-efficacy (that is, low perceived ability to meet the elevated competence expectations associated with managerial roles) seek to minimize voice as a way of compensating for a threatened ego. The results of two studies support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
478
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(500 citation statements)
references
References 85 publications
17
478
0
5
Order By: Relevance
“…For example, companies can achieve more positive outcomes by disclosing information on corporate social responsibility (Burke and Logsdon 1996, Dhaliwal et al 2011, Du et al 2007, privacy practices and policies (Pan andZinkhan 2006, Tsai et al 2010), and executive compensation (Lo 2003). Encouraging employee and consumer voice by allowing the co-creation of products (Franke et al 2013) and seeking constructive feedback (Fast et al 2014) could also help satisfy multiple stakeholders.…”
Section: Seeing and Being Seen: Transparency Perceptions And Performentioning
confidence: 99%
“…For example, companies can achieve more positive outcomes by disclosing information on corporate social responsibility (Burke and Logsdon 1996, Dhaliwal et al 2011, Du et al 2007, privacy practices and policies (Pan andZinkhan 2006, Tsai et al 2010), and executive compensation (Lo 2003). Encouraging employee and consumer voice by allowing the co-creation of products (Franke et al 2013) and seeking constructive feedback (Fast et al 2014) could also help satisfy multiple stakeholders.…”
Section: Seeing and Being Seen: Transparency Perceptions And Performentioning
confidence: 99%
“…To understand what may promote or discourage employees from speaking up to their leaders, most of the existing voice research has taken a between-individual approach to explore the antecedents of voice (Morrison, 2011). These studies have identified employee characteristics, such as self-esteem and dispositional factors (e.g., LePine & Van Dyne, 2001), and leader characteristics, such as openness to change (e.g., Detert & Burris, 2007;Liu, Zhu, & Yang, 2010) and leadership styles (e.g., Fast, Burris & Bartel, 2014;Tangirala & Ramanujam, 2012;Walumbwa & Schaubroeck, 2009), as important predictors of voice.…”
mentioning
confidence: 99%
“…Moreover, when employees highlight a need for improvement, employees implicitly emphasize issues that managers may have overlooked (Burris, 2012) and thus indirectly raise questions about managers' credibility and competence. Given the challenge inherent in voice, managers do not always welcome voice and may react defensively by punishing employees for speaking up or denigrating their input (e.g., Burris, 2012;Fast et al, 2014;Seibert et al, 2001). As a result, employees often fear that expressing their ideas, opinions, or concerns may cause negative personal repercussions such as receiving low performance evaluations, being viewed as troublemaker, as well as damaging personal relationships at the workplace (Detert & Treviño, 2010;Grant, 2013;.…”
Section: Challenging Nature Of Voice and Efficacy-safety Calculusmentioning
confidence: 99%
“…Over the past years, there has been growing scholarly interest in exploring factors that affect managers' reactions to voice. Studies have shown that voice frequency (e.g., Seibert, Kraimer, & Crant, 2001), the attributes of people involved (the voicing employee and the manager; e.g., Fast, Burris, & Bartel, 2014;Sijbom, Janssen, & Van Yperen, 2015a, 2015b, and the attributes of the voice message (e.g., Burris, 2012) affect managers' reactions to voice.…”
Section: General Introductionmentioning
confidence: 99%
See 1 more Smart Citation